2013
DOI: 10.7751/cunninghamia.2013.13.003
|View full text |Cite
|
Sign up to set email alerts
|

Plant communities of the upper Murrumbidgee catchment in New South Wales and the Australian Capital Territory.

Abstract: Native vegetation of the upper Murrumbidgee catchment in southeast NSW and the Australian Capital Territory (ACT) was classified into 75 plant communities across 18 NSW Vegetation Classes within nine Structural Formations. Plant communities were derived through numerical analysis of 4,106 field survey plots including 3,787 plots from 58 existing survey datasets and 319 new plots, which were sampled in under surveyed ecosystems. All plant communities are described at a level appropriate for discrimination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The implications of this focus on dominant species is likely to vary depending on the degree to which patterns F I G U R E 6 Posterior distribution of the parameter estimates for beta regression models of expert judgments of the probability of (a) restoration success and (b) low condition in species dominance correlate with overall composition across the landscape. In this study, the dominant overstorey species occurs in a wide range of vegetation communities (Armstrong et al, 2013) and assessing this species alone would over-estimate the true distribution, a pattern consistent with the higher rate of false positives among experts. In this instance a wider range of ecosystems will be protected than was intended, but in other situations the converse could be true, and such outcomes may undermine confidence in ecological community regulations.…”
Section: Expert Opinions Are Strongly Influenced By the Dominant Tree Speciessupporting
confidence: 59%
See 1 more Smart Citation
“…The implications of this focus on dominant species is likely to vary depending on the degree to which patterns F I G U R E 6 Posterior distribution of the parameter estimates for beta regression models of expert judgments of the probability of (a) restoration success and (b) low condition in species dominance correlate with overall composition across the landscape. In this study, the dominant overstorey species occurs in a wide range of vegetation communities (Armstrong et al, 2013) and assessing this species alone would over-estimate the true distribution, a pattern consistent with the higher rate of false positives among experts. In this instance a wider range of ecosystems will be protected than was intended, but in other situations the converse could be true, and such outcomes may undermine confidence in ecological community regulations.…”
Section: Expert Opinions Are Strongly Influenced By the Dominant Tree Speciessupporting
confidence: 59%
“…Other studies have found that experience is not always a good predictor of performance (Burgman et al, 2011). Our facilitated discussions suggested that first-hand experience and prior knowledge of other vegetation classifications (Armstrong, Turner, McDougall, Rehwinkel, & Crooks, 2013;Costin, 1954;Gellie, 2005;Tozer et al, 2010) potentially contribute to individual-specific models of what constitutes CTGW, particularly among some experienced experts. While individual models are potentially valid interpretations of vegetation distribution and ecosystem processes, individuals with strongly held prior opinion may be less receptive to the detail of the Final Determinations, which may not be helpful when interpreting legally binding community descriptions.…”
Section: Expert Classification Ratesmentioning
confidence: 71%
“…There are two dominant native perennial grass types within our study region: Themeda triandra (C 4 ) dominated and Austrostipa / Rytidosperma spp . (C 3 ) dominated, which differ in community composition (Armstrong, Turner, McDougall, Rehwinkel, & Crooks, ) and might therefore have different responses to mowing. Thus, to quantify dominant grass type, we also recorded the percentage cover of these grass taxa to the nearest 10% within each subplot.…”
Section: Methodsmentioning
confidence: 99%
“…The second operation targeted fallow deer (Dama dama) in the Australian Capital Territory (ACT), over 4 days in June 2019 (Operation B). The operational area is characterised by native grasslands, Pinus radiata plantations and areas of native woodland (primarily red stringybark (Eucalyptus macrorhyncha) and scribbly gum (Eucalyptus haemastoma), as well as red-anthered wallaby grass (Rytidosperma pallidum), tall grass-shrub dry sclerophyll open forest on loamy ridges and grassy woodland (Armstrong et al 2013;ACT Government GeoHub 2018). The climate is temperate, and there was sheep and cattle grazing on some properties.…”
Section: Study Areas and Speciesmentioning
confidence: 99%